Identification of risk factors for myocardial injury in acute ischemic stroke with diabetes mellitus: a retrospective cohort study on stroke-heart syndrome - Pu, Huijuan; Wang, Yumin; Zhao, Guoping; Shi, Binbing; An, Ni; Zhang, Changxi; Liu, Jie; Wu, Wanling; Zhu, Hong; Li, Lei; Pan, Defeng (Frontiers in Stroke, 2025)
BackgroundIschemic stroke (IS) causes significant death and disability. Stroke-Heart Syndrome (SHS) involves cardiovascular complications, worsening outcomes. Diabetes mellitus (DM) increases the risk of myocardial injury following IS. This study explores risk factors for myocardial injury in acute ischemic stroke (AIS) with DM patients to improve early identification and prevention.MethodsThis is a retrospective cohort study. Inclusion criteria: neuroimaging-confirmed AIS, admission within 72 h, and measured cardiac troponinT (cTnT) levels. Exclusion criteria included acute hemorrhagic stroke, other cTnT elevation causes, severe organ failure, infections, malignancies, and missing data. Logistic and LASSO regression analyses identified independent risk factors for myocardial injury.ResultsMyocardial injury occurred in 194 patients. Independent risk factors identified were coronary heart disease (CHD), insular cortex lesions, peak brain natriuretic peptide precursor (peak NT-proBNP), C-reactive protein (CRP), and higher National Institutes of Health Stroke Scale (NIHSS) scores. These factors were significantly associated with myocardial injury and ROC analysis showed that the AUC for CHD was 0.621, the AUC for insular cortex lesions was 0.648, the AUC for NIHSS score was 0.726, the AUC for peak NT-proBNP was 0.816 and the AUC for CRP was 0.764. Subgroup analysis suggested that reperfusion therapy was associated with increased myocardial injury risk in various patient subgroups.ConclusionCHD, insular cortex lesions, peak NT-proBNP and CRP levels, and higher stroke severity (NIHSS score) are significant risk factors for myocardial injury in AIS patients with DM.